Study of Cooperative Games and Its Fuzzification (International Journal of Scientific Research in Science and Technology, 2025)
In this paper we present cooperative games and its fuzzification. A cooperative game (or coalitional game is usually described by a set of players and a characteristics function. In a transferable utility games only one number is attached to each coalition. Cooperative games are useful in considering profit allocation among multiple decision makes who cooperate with each other.